2002
DOI: 10.1046/j.1469-7580.2002.00052.x
|View full text |Cite
|
Sign up to set email alerts
|

Composite cellular defence stratagem in the avian respiratory system: functional morphology of the free (surface) macrophages and specialized pulmonary epithelia

Abstract: Qualitative and quantitative attributes of the free respiratory macrophages (FRMs) of the lung -air sac systems of the domestic fowl (Gallus gallus variant domesticus) and the muscovy duck (Cairina moschata) were compared with those of the alveolar macrophages of the lung of the black rat (Rattus rattus). The birds had significantly fewer FRMs compared to the rat. In the birds, the FRMs were found both in the lungs and in the air sacs. Under similar experimental conditions, the most robust FRMs were those of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
72
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(77 citation statements)
references
References 37 publications
4
72
0
1
Order By: Relevance
“…of the lung but also from the air sacs as elegantly shown in domestic fowls and ducks [55]. Differences in the sampling technique as well as in the chicken strains and immune status of the birds may account for the variable results obtained within [76] and between studies.…”
Section: The Phagocyte System Of the Avian Lung And Air Sacsmentioning
confidence: 97%
See 3 more Smart Citations
“…of the lung but also from the air sacs as elegantly shown in domestic fowls and ducks [55]. Differences in the sampling technique as well as in the chicken strains and immune status of the birds may account for the variable results obtained within [76] and between studies.…”
Section: The Phagocyte System Of the Avian Lung And Air Sacsmentioning
confidence: 97%
“…Whereas Klika et al [37] did not find evidence for the migration of FARM from the interstitial tissue to the surface of the conducting airways other investigators reported the opposite [25,77]. Nganpiep and Maina [55] compared the number of macrophages obtained by first and subsequent lung lavages and found a clear increase in cell numbers. The authors concluded that these cells emanated through efflux from the subepithelial compartment or even from the vascular system itself.…”
Section: The Phagocyte System Of the Avian Lung And Air Sacsmentioning
confidence: 98%
See 2 more Smart Citations
“…Adjacent to the muscle fibers that form the parabronchi, the lumen is bordered by 74.3 stained cells, and these cells are expected to act as mammalian alveolar MPh (Jeurissen et al 1994). Epithelial cells lining the atrial muscles, the atrial floor and the infundibulae have been shown to be phagocytic and may therefore play a role in the defence of the thin, extensive and highly vulnerable tissue barrier (Nganpiep and Maina 2002). It is unclear if phagocytosed material is presented to the local immune system in the BALT, or in the follicles present in the interstitium between parabronchi or if it is transported to the spleen or a combination of these option depending on the antigen.…”
Section: The Phagocyte System Of the Rtmentioning
confidence: 99%